Role of isoprostanes in human male infertility. (2nd September 2020) - Signorini, Cinzia; Moretti, Elena; Collodel, Giulia
ABSTRACT: One of the major causes of defective sperm function is oxidative stress, which limits the fertilizing potential of these cells as the result of collateral damage to proteins and lipids in the sperm plasma membrane. On this point, a derangement of both generation and neutralization of reactive oxygen species (ROS) is a recognized cause of male infertility. Antioxidant protection in sperm has been widely investigated, as well as the sperm composition of fatty acids (FA), which represents the preferred substrate for ROS, most frequently linked to the disease-related infertility. Isoprostanes are compounds derived from free radical-mediated oxidation of FAs. As such, they are considered an index of lipid oxidative damage and lipid mediators. This article discusses the role of isoprostanes as relevant factors both to sperm FA composition and sperm membrane integrity. Additionally, isoprostane's influence on sperm quality is reviewed. With reference to male reproductive dysfunction, increasing evidence indicates isoprostanes, detectable in biological fluids or sperm membrane, as the specific index of 1) exposure to chemical etiological agents, 2) oxidative damage, 3) reduced antioxidant response, and 4) sperm immaturity. Abbreviations: OS: oxidative stress; ROS: reactive oxygen species; PUFAs: polyunsaturated fatty acids; ARA: arachidonic acid, F2 -IsoPs; F2 -isoprostanes, PLA2 : phospholipase A2 ; NADPH: nicotinamide adenine dinucleotide phosphate; IVF: in vitro fertilization